PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi karyawan bagian produksi CV. Nida Food Wonosobo) - Nashafa, Pamila; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2016)
The research aims to examine and analyze the influence of transformational leadership style and compensation toward performance of employee in CV. Nida Food. Data collected through distribution of questionnaires and it is implemented to CV. Nida Food’s 50 employee. Analysis of data in this research using the help of SPSS version 17. A sampling technique uses a Slovin method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic assumption test and double linear regression analysis, to verify and to prove the research hypothesisThe result of this research shows that there is no significant influence between transformational leadership style and compensation for employees performance in Nida Food. Meanwhile Nida Food employees performance influenced by leaderhip and compensation takes around 1,30% and the rest 98,7% are determined by other factors and variables which are not the main concern of this research